Planting and Irrigation Methods for Cotton in Southern Xinjiang, China†. (5th May 2016) - Zhong, Ruisen; Tian, Fuqiang; Yang, Pengnian; Yi, Qiuxiang
Abstract: In order to provide a scientific technology reference for cotton planting and management in southern Xinjiang that is based on practical investigations and existing achievements, cotton planting and irrigation methods were divided into four groups. In addition, the applications of these methods are discussed. The four types of cotton‐planting methods are as follows: (i) one film + no pipes + four rows; (ii) one film + single pipe + four rows; (iii) one film + double pipes + four rows; and (iv) double films + double pipes + four rows. The four types of cotton field irrigation methods are as follows: (i) winter irrigation (spring irrigation) + routine flooding irrigation; (ii) winter irrigation (spring irrigation) + drip irrigation under mulch; (iii) seeding after drip irrigation + drip irrigation under mulch; and (iv) dry seeding before drip irrigation + drip irrigation under mulch. The planting and irrigation methods for cotton supplement each other and are coupled based on local climate, soil, surface water and groundwater conditions. In addition, the most scientifically reasonable, cost‐effective, water‐saving and productive methods must be selected. Copyright © 2016 John Wiley & Sons, Ltd.